Women and Digital Financial Inclusion in Indonesia as Emerging Market - Soekarno, Subiakto; Mambea, Indra Yudha; Setiawati, Marla (International Review of Management and Marketing, 2020)
Digital financial inclusion is digital access to and use of formal financial services. This paper aims to examine the significance of gender dimension in digital financial inclusion in Indonesia as an Emerging Market. By using surveys, we expect to relate women and digital financial inclusion. The ordinal logistic regression model was used as a method to model one of the key variables, gender. The result concluded that women as the gender we concerned gives a significant impact to behavioral intention that represents the digital financial inclusion. Keywords: women digital financial inclusion, financial services, gender dimension JEL Classifications: G4, I20 DOI: https://doi.org/10.32479/irmm.10212